POTENSI NIRA KELAPA SEBAGAI BAHAN BAKU BIOETANOL - Wijaya, I Made Anom Sutrisna; Arthawan, I Gusti Ketut Arya; Sari, Anis Novita (Bumi Lestari, 2012)
The objective of this reseach was to determine the frequency of destilation in production of bioethanol produced from coconut sap, as well as to determine the quality of bioethanol. Three steps were conducted in production of bioethanol : the first step was fermentation of coconut sap in room temperature for two days, the second step was destilation of fermented coconut sap (tuak) at 780C to make the alcohol content ?94%, and the last step was determination of the quality of bioethanol. The result showed that the frequency of destilation in production of bioethanol from coconut sap was 14 times with alcohol content 92,17%. The yield was 4,83%, the quality of bioethanol was ethanol content 95,13%, density 0,766 kg/ltr, specific gravity 0,786, API gravity 48,61 and heat energy 11.211,94 kkal/kg. In conclution, the bioethanol produced from coconut sap in this research met with Indonesian Standard National (SNI) of bioethanol.
Keywords: distillation; bio-ethanol; coconut sap; SNI bio-ethanol; API gravity